The Epistemic Benefits of Diversifying the Philosophy of Religion - Lougheed, Kirk (European journal for philosophy of religion, 2022)
There have been recent calls to expand contemporary analytic philosophy of religion beyond the oft implicitly assumed Christian tradition. Instead of exploring moral reasons to expand the discipline, I argue that there are strong epistemic reasons to favour diversifying the philosophy of religion. Increasing diversity is likely to increase disagreement, and there are epistemic benefits to be gained from the existence of disagreement. I argue that such considerations quite clearly apply to the philosophy of religion, and as such that there are epistemic reasons to diversify the field. I conclude by offering a number of practical steps we can take towards achieving this end which are relatively easy to implement.